Mutations of the Androgyne: Its Functions in Early Modern French Literature - Rothstein, Marian (The sixteenth century journal, 2003)
The Androgyne takes its name from the myth in Plato's "Symposium". Gen. 2, where man and wife are to be one flesh, gives us the marriage androgyne. From Gen. 1, in which Adam is male and female, we have another sort of androgyne, this one purely of the spirit. Drawing on these sources, Renaissance writers made use of the androgyne as a figure of desire (both heterosexual and homosexual), of marital fidelity and marital infidelity, and of the soul seeking union with the divine. This article examines the uses of the androgyne in sixteenth-century French literature, both diachronically, tracing changes in the use of the figure over time, and synchronically, studying the purposes it served. It is also concerned with charting changing expectations of reception, clarifying our understanding of what the authorial audience is expected to know.